Application of the DMAIC tool for the improvement of the ship careening process in a Latin American shipyard - Mendieta Villalba, Nadia Mercedes; Tingo Soledispa, Marjorie Verónica; Rodríguez Espinoza de los Monteros, Amalia Elvira; Peña Montoya, Pedro Gerardo (LACCEI, 2025)
Abstract– Six Sigma is a work methodology that allows companies to measure their operational efficiency, reduce defects in their processes, and improve their management. It is based on quality control and seeks to reduce variability and defects in the delivery of a product or service to the customer. The methodology can be applied to any type of process and organization.This article deals with the application of DMAIC tool in the process of ship careening in a Latin American shipyard, Ecuadorian Navy Shipyards (Astinave). The research was conducted to optimize response times in the management of the development of maintenance, careening, and repair activities. Currently, the process takes an average of 17 to 21 days.The article analyzes the delay in the arrival of materials and other inconveniences that result in the accumulation of unproductive time in the process. The DMAIC model was adapted, which stands for define, measure, analyze, improve, and control, for which different statistical and quality tools were used to obtain savings in the stay of the vessels.The sequence of the process was first to diagnose the initial situation, for which statistical data of the vessels that entered the shipyard were used, then the measurement method was determined using techniques and tools that helped to identify causes for the subsequent analysis of the problems detected. Objectives were achieved with performance metrics. Finally, an action plan was proposed to provide quality, solutions, and control of the problems.